2015
DOI: 10.1089/bfm.2014.0086
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Use During Breastfeeding

Abstract: No increase in adverse long-term outcomes was found in colchicine-exposed breastfed infants. Our data support continuation of breastfeeding in women treated with colchicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…Colchicine is safe during pregnancy (Skorpen 2016) and lactation (Herscovici et al 2015) based on data from the rheumatologic literature. Intravenous immunoglobulins are also considered a safe therapy during both pregnancy and lactation (Butler et al, 2014, Murase et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Colchicine is safe during pregnancy (Skorpen 2016) and lactation (Herscovici et al 2015) based on data from the rheumatologic literature. Intravenous immunoglobulins are also considered a safe therapy during both pregnancy and lactation (Butler et al, 2014, Murase et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the included drugs have a well‐established safety profile for use during nursing, making them a much safer option for nursing women with COVID‐19. Although colchicine was present in the milk sera of nursing mothers, its concentration was negligible, and it was safe to use during nursing (Ben‐Chetrit, 2018 ), and no side effects or long‐term effects were observed among the breastfeeding infants (Herscovici et al, 2015 ). According to the drug and lactation database in the US's national library of medicine, several reports and studies for breastfeeding mothers using prednisone or methylprednisolone showed no side effects on the infants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the drug inhibits neutrophil migration to sites of inflammation, thereby serving as an anti-inflammatory [ 118 ]. Colchicine use in pregnancy and breastfeeding is controversial with an FDA class C recommendation, although recent data suggests a more lenient approach regarding its usage during pregnancy and breastfeeding [ 119 , 120 , 121 ]. Side effects include a variety of symptoms ranging from mild and frequent (e.g., gastrointestinal symptoms such as vomiting, nausea, and abdominal pain) to rare and serious (e.g., hematological dyscrasia, myalgia, neuropathy, confusion, and convulsions) [ 117 , 122 , 123 , 124 , 125 ].…”
Section: Current Prophylaxis Options For Covid-19mentioning
confidence: 99%